PENGARUH STOCK SPLIT TERHADAP LIKUIDITAS SAHAM YANG DIUKUR DENGAN BESARNYA BID-ASK SPREAD DI BURSA EFEK JAKARTA - Sri Fatmawati; Marwan Asri (Faculty of Economics and Business, Universitas Gadjah Mada, 1999)
It is widely believed that stock splits are purely cosmetic, since thecorporation's cash flows are unaffected, each shareholder retains his proportionateownership and the claims of other classes of security holders are unaltered. Althoughstock splits appear to be purely cosmetic changes, research shows real effectsassociated with them. Despite extensive study, controversies still abound in theliterature about these effects. These controversies include whether stock splits affectshareholder wealth, change a stock risk, improve liquidity, and provide signals to themarket. The objective of this research is to verify empirically that stock splits relatethose real effects especially stock liquidity as measured by bid-ask spread.This research examines thirty companies which did stock splits in JakartaStock Exchange during July 1995 to June 1997. A paired-difference test is used totest some hypothesis about the difference between two population means for stockprince, variance, trading volume, turnover volume, and bid-ask spread variables.Furthermore, the multiple regression analysis is used to examine the relation of stockprice, trading volume, stock volatility to bid-ask spread.Overall, the results of this research indicate that there are significantdifferences among stock price, turnover volume, and bid-ask spread for before andafter the listing date. Besides that, the difference of bid-ask spread is affected bystock price, volatility, and trading volume.